From classroom to real word: Researching into how Chinese as a Foreign Language beginner learners use Social Networking technology to develop intercultural communicative competence in UK secondary schools - Ruan, Jingjing (2019)
This research aimed to explore the teaching and learning of intercultural communicative competence (ICC) in a Chinese as a foreign language (CFL) context and to understand how social networking (SN) technology can contribute to CFL beginner learners’ ICC development. The research involved a longitudinal exploratory case study (2015-2017), in which the case was a single General Certificate of Secondary Education (GCSE) Mandarin class and the participants consisted of nine CFL beginner learners in a comprehensive secondary school in the Midlands of the UK. The research question focuses on how CFL beginner learners used social networking technology to develop their ICC and to communicate with their language partners from a link school in China. The research was carried out in the interpretive tradition in that it sought a rich and detailed understanding of the case by examining aspects of it in depth. This exploratory case study was intended to provide a trustworthy and transparent account of CFL learners’ use of social networking tools around genuine communication in Chinese. The focus of the study was to explore how a group of GCSE Mandarin students’ use of social networking technology contributed to their ICC development in a collaborative Community of Inquiry learning environment. Methods of data collection included participant observation, field notes, questionnaires, and semi-structured interviews with students. The Community of Inquiry analysis framework (Garrison et al., 2000) and Byram’s (1997) ICC model were used as the base of the analysis of students’ online exchange and intercultural communication. The findings of this case study showed that Social Presence was the category of presence most often identified in the current Community of Inquiry created by GCSE Mandarin learners, followed by Cognitive Presence, and then Teaching Presence. The use of social networking technology was motivating and solved real-life problems (i.e. exchange visits). The intercultural tasks II in this exchange project promoted purposeful communication which generated unplanned topics on real-life events that were of interest to participants. The multimodal affordances of social networking tools played a crucial role in participants’ continuous participation and increased motivation in a Community of Inquiry. The informal characteristic of online conversation in this case study was in line with the “third place” concept, and non-linguistic features of social networking tools contributed to participants’ intercultural experience and ICC development. It is argued that translanguaging and collaborative learning in a Community of Inquiry could be a practical and useful approach to enable CFL beginner learners to become comfortable using the target language step by step while exploring the intercultural aspects of the target culture and community. In terms of GCSE Mandarin academic skills, the group of participants reported that they developed Mandarin writing and reading skills more than speaking and listening skills by using social networking technology. To conclude, social networking tools could help to create a Community of Inquiry where CFL beginner learners can develop real-world intercultural communicative competence through collaboration and exchange with language partners to become globally competent “intercultural speakers” (OECD, 2018).